2013
DOI: 10.1002/ejic.201201489
|View full text |Cite
|
Sign up to set email alerts
|

Hydroboration of Alkyne‐Functionalized 1,3,2‐Benzodiazaboroles

Abstract: Reactions of equimolar amounts of dicyclohexylborane (DCB) with a series of 2‐alkynyl‐1,3‐diethyl‐1,3,2‐benzodiazaboroles R–C≡C–B(NEt)2C6H4 (1: R = nBu, 2: R = tBu, 3: R = Ph, 4: R = p‐Me2NC6H4, 5: R = p‐MeOC6H4) regioselectively afforded the 1,1‐diborylalkenes (Z)‐R(H)C=C{(B{NEt}2C6H4)B(c‐C6H11)2} (7a–11a) as the result of a cis‐addition of the BH bond of the borane to the C≡C triple bond in compounds 1 to 5. In contrast to this, reaction of Me3Si–C≡C–B(NEt)2C6H4 (6) with HB(c‐C6H11)2 yielded a 2.5:1 mixture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Molecules 2020, 24, x FOR PEER REVIEW 26 of 30 In 2013, Weber et al reported the hydroboration of 2-alkyl-and 2-aryl-ethynyl-1,3,2benzodiazaboroles with dicyclohexylborane (DCB) under metal-free conditions at room temperature, affording the cis-1,1-bis(boryl)alkene 82 as a major regioisomer, with quantitative yields [50]. Interestingly, they also observed the hydroboration of 2-silylethynyl-1,3,2-benzodiazaborole with DCB, which afforded 1,1-bis(boryl)alkene (82) as a minor regioisomer and trans-1,2-bis(boryl)alkene as a major regioisomer (83), with quantitative yields (Scheme 33) [50]. Scheme 33.…”
Section: Unsymmetrical Sp 2 -Centered 11-bis(boron) Compounds: Synthmentioning
confidence: 99%
“…Molecules 2020, 24, x FOR PEER REVIEW 26 of 30 In 2013, Weber et al reported the hydroboration of 2-alkyl-and 2-aryl-ethynyl-1,3,2benzodiazaboroles with dicyclohexylborane (DCB) under metal-free conditions at room temperature, affording the cis-1,1-bis(boryl)alkene 82 as a major regioisomer, with quantitative yields [50]. Interestingly, they also observed the hydroboration of 2-silylethynyl-1,3,2-benzodiazaborole with DCB, which afforded 1,1-bis(boryl)alkene (82) as a minor regioisomer and trans-1,2-bis(boryl)alkene as a major regioisomer (83), with quantitative yields (Scheme 33) [50]. Scheme 33.…”
Section: Unsymmetrical Sp 2 -Centered 11-bis(boron) Compounds: Synthmentioning
confidence: 99%
“…Two-step procedures starting from terminal alkynes (Scheme 2B) 1618 and methods involving stoichiometric amounts of organolithium reagents (Scheme 2C) have also been reported. 19,20 However, these approaches suffer from low volumetric throughput and poor functional group compatibility, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Several synthetic methods for accessing 1,1-diborylalkenes have been developed. [1][2][3][4] Specifically,4 0years ago Matteson reported the synthesis of 1,1-diborylalkenes through an addition reaction of triborylmethyllithium to carbonyl compounds (Scheme 1a). [2] More recently,Shimizu, Hiyama, and co-workers reported ar eaction between bis(pinacolato)di-boron and 1-bromo-1-lithioalkenes,w hich were prepared from 1,1-dibromoalkenes by means of Br-Li exchange (Scheme 1b).…”
mentioning
confidence: 99%